Средоточия политической жизни в демократических Афинах - Монева, С. Г. (Давнина. Харківський історико-археологічний щорічник, 2016)
Резюме Монева С. Осереддя політичного життя у демократичних Афінах Статтю присвячено визначенню та характеристиці пунктів, де проходили Народні збори, відбувалися засідання Буле, Ареопагу та Геліеї в стародавніх Афінах у час розквіту демократичного полісного ладу. На думку автора, є ґрунтовні підстави пов’язувати діяльність цих керівних органів Афінського полісу з певними місцями та спорудами, відкритими під час археологічних розкопок Афін. Разом із тим, наголошується у статті, внаслідок надзвичайних обставин, робота згаданих керівних органів могла проходити і в інших місцях, що слід обов’язково враховувати, відновлюючи картину політичного життя в демократичних Афінах. Ключові слова: Афінська демократія, Пнікс, Буле, Ареопаг, Геліея. Summary S. Moneva. Ccentre Points of the Political Life in the Democratic Athens The basic political bodies of the Athenian democratic polis are presented in this paper: the Athenian popular assembly, the Boule, the Areopagos Council and the Heliaia. The author has set herself the main task of localizing the places where the political functions of these bodies were carried out. It is ascertained in the paper that the meetings of the Athenian popular assembly took place on Pnyx Hill, the members of the Boule met in the Bouleuterion, and the of the Areopagos Council — on Ares’ Hill. The place of the meetings of the Heliaia is localized in the court premises on the Agora. The author draws the conclusion that there are good reasons to connect the activities of the bodies in question with certain places or buildings in Athens. At the same time one should take into consideration the possibility that the Athenians sometimes changed the places of the meetings of these institutions under reasons that could be defined as urgent, extraordinary or forced by the circumstances. Key words: Athenian democracy, Pnyx, Boule, Areopagos, Heliaia.